2022
DOI: 10.15294/biosaintifika.v14i2.36530
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcode of Red Junglefowl Gallus gallus L, 1958 (Aves: Phasianidae) of Sumatra Based on Mitochondrial COI DNA Gene

Abstract: Genetic data of red junglefowl (Gallus gallus) from southern Sumatra is valuable for conservation efforts in Indonesia. A mitochondrial COI DNA gene sequencing was performed to elucidate its genetic character, single nucleotide polymorphism, genetic distance, and phylogeny. Blood samples (±0.5 ml) from 20 individuals of Gallus gallus were taken from the living collections of the people of Bengkulu Province (Central Bengkulu Regency and Seluma Regency) and South Sumatra Province (North Musi Rawas Regency) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Based on the results of the analysis presented in Table 5, the minimum interspecific genetic distance is 0.068 (6.8%), the maximum is 0.123 (12.3%), and the mean is 0.097 (9.0%). Our findings are comparable to those of prior research, particularly that utilized the mtDNA COI gene to determine genetic distances between species within the same genus (Efe et al, 2009;Cai et al 2010;Arif et al 2011;Huang and Tu, 2016;Susanti et al 2018;Jarulis et.al., 2018;Jarulis et al, 2021;Jarulis et al, 2022). Waugh (2007) indicated that the interspecific genetic distance should be larger than 5.0% for identification results to be more precise.…”
Section: Genetic Distancementioning
confidence: 99%
“…Based on the results of the analysis presented in Table 5, the minimum interspecific genetic distance is 0.068 (6.8%), the maximum is 0.123 (12.3%), and the mean is 0.097 (9.0%). Our findings are comparable to those of prior research, particularly that utilized the mtDNA COI gene to determine genetic distances between species within the same genus (Efe et al, 2009;Cai et al 2010;Arif et al 2011;Huang and Tu, 2016;Susanti et al 2018;Jarulis et.al., 2018;Jarulis et al, 2021;Jarulis et al, 2022). Waugh (2007) indicated that the interspecific genetic distance should be larger than 5.0% for identification results to be more precise.…”
Section: Genetic Distancementioning
confidence: 99%